ORGANIZATIONAL AND LEGAL FOUNDATIONS OF CONDUCTING EXTERNAL AUDIT OF THE ANNUAL REPORT ON BUDGET PERFORMANCE - Vitaliy V. Perov; Evgeniya V. Klicheva (Вестник Российского экономического университета имени Г. В. Плеханова)
External audit of the annual report on budget performance is the most versatile method of conducting external finance control during which both control and expert-analytical steps are taken aimed at raising efficiency of using public resources. The article discusses foundations of standardization of procedures carried out within the frames of external audit of the annual report on budget performance; studies the experience of the Control and Account Chamber of Moscow in this field; identifies problems in organization and conducting external finance audit carried out by control and account bodies. It also shows causes of violations found during control steps. The authors formulate proposals aimed at improvement of external finance audit in order to ensure positive dynamics of figures of social and economic development in regions of the Russian Federation.